A relevância da valência afetiva no acesso lexical de palavras isoladas em português brasileiro - Veras, Fernanda Marabelly de Oliveira (2024)
Our linguistic ability is strongly linked to the mechanisms of our long-term memory. The mental lexicon is one of these mechanisms specialized in storing a large part of linguistic knowledge. Understanding the formation of the lexicon and accessing its linguistic database are complex tasks due to the integration of variables intrinsic to the speaking individual and related to the language architecture itself (neural networks, executive functions, level of instruction), as well as variables intrinsic to words (lexical, orthographic and morphological properties), among which we can mention lexical frequency, number of letters, syllables, and grammatical class, characteristics extensively evaluated in terms of their impact on adequate access to the mental lexicon. However, the components of a language (words) can transmit information that is linked to affective values (valence) for the individual (a fundamental aspect of human experience and closely linked to cognition), capable of evoking emotions that influence cognitive and behavioral processes. Although numerous models seek to explain lexical formation and access, it is still unclear how the affective value of a word interferes with this process. Therefore, the main objective of this study was to evaluate the extent to which valence and its interaction with lexical and morphological properties influence the linguistic processing of isolated words in Brazilian Portuguese (BP). To this end, the study was conducted in three stages: i) translation of a word bank into BP from foreign emotional lexicons; ii) validation of translated words through the judgment of valence and excitability, contributing to the development of a BP mini lexicon containing the mentioned metrics; and iii) carrying out a Lexical Decision Task experiment, whose stimuli were words from the second stage. The results indicate that word valence assessment occurs in the background. In other words, its interference in reaction times would be associated with operations and combinations between facilitation and slowdown resulting from lexical and orthographic characteristics. Furthermore, this influence becomes more significant as response selection loses its automation and becomes a more conscious process, manifesting itself especially for words classified as verbs and with a negative value. Therefore, new studies in BP are encouraged to include the emotional value of the word as a determining factor capable of influencing recognition and lexical access.